Verification of the shear resistance of UHPFRC beams – Design method for the German DAfStb Guideline and database evaluation. (15th February 2023) - Metje, Kevin; Leutbecher, Torsten
Highlights: Extensive UHPC and UHPFRC shear database including 208 experiments. Shear design method for UHPFRC beams based on EC 2 and German DAfStb Guideline. Distinction between I-shaped and compact cross-section for economic reasons. Conversion factors are proposed for standardization of material parameters. Database-driven statistical evaluation provides for high model reliability. Abstract: This contribution focuses on the verification of the shear resistance of Ultra-High Performance Fiber-Reinforced Concrete (UHPFRC) beams. A verification method following Eurocode 2 and the German DAfStb Guideline „Steel Fibre Reinforced Concrete" is presented, which superimposes the shear resistance of a member without shear reinforcement, the shear resistance provided by stirrups, and the contribution of the fibers activated in the shear crack. With regard to the contribution of the fibers, the verification method differentiates between members with I-shaped and approximately rectangular solid cross section. This provides a more favorable design of members with I-shaped cross section. Reliability of the design approach is statistically evaluated by means of a total of 208 shear tests on UHPC and UHPFRC beams with different configuration. For 133 tests on beams with I-shaped cross section the ratio between ultimate shear force from experiment V exp and theoretical shear resistance V cal shows a mean value of X̅  = 1.48 and a 5 % quantile of Q 0, 05  = 0.94. For 75 tests on beams with approximately rectangular solid cross section the results are X̅  = 1.59 and Q 0, 05  = 0.94. For all 208 tests included in the database X̅  = 1.52 and Q 0, 05  = 0.94 are obtained. Based on the statistical parameters it is concluded that the prediction model is sufficiently reliable for being considered with the forthcoming German DAfStb Guideline on Ultra-High Performance Concrete.